2019
DOI: 10.1002/fsn3.1059
|View full text |Cite
|
Sign up to set email alerts
|

The influence of yeast level and fermentation temperature on Ochratoxin A decrement during bread making

Abstract: Ochratoxin A (OTA) occurrence in cereals is a permanent challenge in human health. In recent years, some studies have focused on the role of yeasts as adsorbing tools to eliminate OTA. The aim of the current research was to study the effects of different variables including Saccharomyces cerevisiae amount and the fermentation temperature on the reduction of OTA during bread baking. For this purpose, the OTA was spiked to the flour and then the bread was prepared. OTA levels in flour, dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…It could be due to the lower yeast concentration and shorter fermentation time. Moreover, other studies (Mozaffary, Milani, & Heshmati, 2019;Valle-Algarra et al, 2009) on mycotoxin reduction during wheat bread fermentation showed increased in fermentation time and yeast concentration could have more effect on reducing mycotoxins, that was in good agreement with our results.…”
Section: Effect Of Fermentation On Afbsupporting
confidence: 93%
“…It could be due to the lower yeast concentration and shorter fermentation time. Moreover, other studies (Mozaffary, Milani, & Heshmati, 2019;Valle-Algarra et al, 2009) on mycotoxin reduction during wheat bread fermentation showed increased in fermentation time and yeast concentration could have more effect on reducing mycotoxins, that was in good agreement with our results.…”
Section: Effect Of Fermentation On Afbsupporting
confidence: 93%
“…Several authors [2,18,36,37] have proposed a specific selection of wine yeasts that are able to get a selective removal of OTA. However, strains which remove more OTA, also adsorb more colour and phenolics from wine.…”
Section: Discussionmentioning
confidence: 99%
“…Armando et al [ 39 ] demonstrated the ability of two yeast strains, S. cerevisiae RC008 and RC016, to inhibit the growth of Aspergillus carbonarius and F. graminearum , and reduce their production of the mycotoxins ochratoxin A (OTA), ZEA, and DON. Mozaffary et al [ 40 ] confirmed that during dough fermentation baker’s yeast S. cerevisiae was able to reduce the amount of OTA in wheat flour by about 60%. Piotrowska and Żakowska [ 41 ] showed that baker’s yeast and lactic acid bacteria mixed culture were found to be efficient in toxin degradation, which could be explained by the synergistic relationship between these microorganisms in the baker’s sourdough.…”
Section: Discussionmentioning
confidence: 99%